Cellulase hydrolyzed Indigofera zolingeriana leaf utilization as a feed ingredient for gourami fingerling - Jefry Jefry; Mia Setiawati; Dedi Jusadi; Ichsan Achmad Fauzi (Jurnal Akuakultur Indonesia)
This study was aimed to evaluate the utilization of hydrolyzed Indigofera zolingeriana by celullase enzyme as the feed ingredient of gourami fish. This study used a completely randomized design which contained three steps, whereas each step contained four treatments and four replications. The first step performed by evaluating the Indigofera leaf meal (ILM) added with cellulase enzyme of 0 g/kg (control), 0.4 g/kg, 0.8 g/kg, and 1.2 g/kg. The second step was the digestibility test of ILM on gourami seeds. The third step was feed evaluation added with ILM as much as 0% (control), 15%, 30%, and 45% against the growth performance on gourami seeds. The gourami seeds used in the second and third steps with a weight of 13.65 ± 0.39 g/seed and 5.95 ± 0.15 g/seed, respectively. The addition of 0.8 g/kg and 1.2 g/kg cellulase enzyme could significantly decrease the crude fiber of ILM with 43.33%, besides having the best value of total, ingredient, protein, lipid, and energy digestibility. The growth performance of gourami seeds given 15% ILM added feed had the best value and insignificantly different from the control feed without ILM addition based on the specific growth rate (SGR), protein retention (PR), and feed efficiency (FE).